1987
DOI: 10.1523/jneurosci.07-11-03474.1987
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies distinguish several differentially phosphorylated states of the two largest rat neurofilament subunits (NF-H and NF-M) and demonstrate their existence in the normal nervous system of adult rats

Abstract: A new panel of greater than 300 monoclonal antibodies (mAbs) was prepared to the high, middle, and low Mr rat neurofilament (NF) subunits (NF-H, NF-M and NF-L, respectively). NF proteins were purified both from native, i.e., phosphorylated rat NFs and from enzymatically dephosphorylated rat NFs. The resulting mAbs were used to biochemically and immunochemically distinguish and characterize distinct and differentially phosphorylated isoforms of NF subunits. By immunoblot, all mAbs specific for NF-L and some mAb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
317
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 486 publications
(340 citation statements)
references
References 26 publications
22
317
1
Order By: Relevance
“…For histological staining, 16-m-thick cryosections were prepared, postfixed 1 hr in 4% paraformaldehyde (PFA) in PBS, and stained by hematoxylin coloration or Bielschowsky's silver impregnation (Cox, 1977). N N-18 (Chemicon International, Temecula, CA; Shaw et al, 1986;Harris et al, 1991) and RMO-44 (Zymed Laboratories, San Francisco, CA) (Lee et al, 1987) monoclonal antibodies were used for immunohistochemistry against N F-M. Axonal growth cones were detected with a monoclonal antibody directed against growth cone-associated protein 43 (GAP43; Chemicon International). Astrocytes and oligodendrocytes were labeled using monoclonal antibodies directed against glial fibrillary acidic protein (GFAP; Chemicon International) and myelin basic protein (MBP; Boehringer Ingelheim).…”
Section: Methodsmentioning
confidence: 99%
“…For histological staining, 16-m-thick cryosections were prepared, postfixed 1 hr in 4% paraformaldehyde (PFA) in PBS, and stained by hematoxylin coloration or Bielschowsky's silver impregnation (Cox, 1977). N N-18 (Chemicon International, Temecula, CA; Shaw et al, 1986;Harris et al, 1991) and RMO-44 (Zymed Laboratories, San Francisco, CA) (Lee et al, 1987) monoclonal antibodies were used for immunohistochemistry against N F-M. Axonal growth cones were detected with a monoclonal antibody directed against growth cone-associated protein 43 (GAP43; Chemicon International). Astrocytes and oligodendrocytes were labeled using monoclonal antibodies directed against glial fibrillary acidic protein (GFAP; Chemicon International) and myelin basic protein (MBP; Boehringer Ingelheim).…”
Section: Methodsmentioning
confidence: 99%
“…Anti-NF antibodies used in this study are well characterized and have been used previously to demonstrate epitopes of NF in neuronal inclusions in AD, Lewy body diseases, and MND [6,19,25,26,32,33,34,35]. In addition, antibodies to α-synuclein [10], cytoskeletal, and other proteins associated with abnormal protein aggregates in neurodegenerative diseases were used in this study.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…Recently, we described α-internexin as a major component of the pathological hallmark of NIFID [5]. Although previous studies have demonstrated the co-localization of NF epitopes in AD, PD, DLB, and MND [19,25,26,28,29,32,33,34,35], no study has demonstrated the presence of α-internexin as a component of the pathological inclusions of any neurodegenerative disease other than NIFID.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One section from each subject was stained with acridine orange to verify the presence of nucleic acids in the tissue (Figure 2). An adjacent section was immunostained with a monoclonal antibody to non-phosphorylated neurofilament (RmdO20; Lee et al, 1987) to identify individual neurons for subsequent single cell analysis. Following in situ transcription, Layer II stellate neurons were dissected and contents were amplified using aRNA amplification (Tecott et al, 1988;VanGelder et al, 1990;Eberwine et al, 1992).…”
Section: Schizophreniamentioning
confidence: 99%